Small-fiber polyneuropathy in leprosy without skin changes: study of 17 cases - Marcos R.G. de Freitas; Osvaldo J.M. Nascimento; Ernestina A.M. Quaglino; Andréia Oliveira; Myrian D. Hahn (Arquivos de Neuro-Psiquiatria)
Leprosy is one of the most common diseases of the peripheral nerves. In some cases there is only neural involvement without skin changes (neuritic form). The neuropathy has often a distal stocking and glove distribution with thermal and pinprick anesthesia and preservation of proprioception. There is no weakness, the tendon reflexes may be preserved and sometimes the nerves are thickened. We reported 17 patients with a predominantly small-fiber polyneuropathy due to leprosy. All patients had distal temperature and pain anesthesia with different individual variations. The tendon reflexes were normal in seven patients and in eight there was thickening of the nerves. The nerve conduction was normal in three patients. Sural nerve biopsy consisted of: 1) inflammatory infiltrates, 2) vacuolated "foamy" cells, 3) fibrosis of endoneurium, perineurium, and epineurium, 4) partial or total loss of nerve fibers, 5) large number of bacilli. We concluded that in countries where leprosy is frequent, nerve biopsy is an obligatory procedure in patients with predominantly small-fiber polyneuropathy.